Ideology and Immigration Patterns in European Union (1988–2015) - Medeiros, Marcelo de Almeida; Figueiredo Filho, Dalson Britto; Batista da Silva, Mariana; Ricardo da Silva, Cinthia Regina Campos; Rosendo da Silva, Sidney José Vasconcelos; Oliveira, Natália Coêlho de Souza (Revista de Sociologia e Política, 2020)
ABSTRACT Introduction: The theory points out to the existence of likely links between party ideology and migratory policies, stating that, in principle, values associated with the right, based on nationalism, tend to, restrict immigration dynamics more than those linked to the axiology of the left, anchored in universalism. Does party ideology affect immigration patterns in the European Union? This paper tests the hypothesis that the greater the values in ideology (right-wing governments), the smaller the number of migrants to that specific country. Materials and Methods: The research design replicates secondary data from both a parliament and government database (ParlGov) and the Comparative Manifesto Project. We also use data from the Global Bilateral Migration Database and Bilateral Migration Matrix. Besides the descriptive statistics, we examine the relationship between ideology and migration flows. We estimated two regression models to deal with the following dependent variables: net migration and refugee population by country or territory of asylum. Results: Using data from ParlGov, Manifesto, and QoG, descriptive statistics has stressed a very heterogeneous cartography of political features, ideology, and migration in European Union countries. The first regression analysis using aggregate data suggests that the greater the values of ideology per country (right-wing oriented), the lower the number of people entering that country. However, the findings from our disaggregated statistical analysis, particularly Model 1, indicate no effect of cabinet ideology on net migration. As for the refugee category for immigrants, our results suggest that right-oriented national governments are less receptive to refugees. Model 2 stated that a one-point increase in ideology is associated with a 13% average reduction in the number of refugees entering the country. Discussion: This study advances our current understanding about the relationship between party ideology and immigration patterns. Nonetheless, the results of the regression analysis show limited evidence in favor of our hypothesis that the more to the right of the ideological spectrum governments are, the lower the number of refugees they will accept. However, this analysis is only meant to show a relationship between ideology and migration. Causal claims should be interpreted with caution. KEYWORDS: European Union; government; ideology; migration; political parties. Padrões de Ideologia e Imigração na União Europeia (1988–2015) RESUMO Introdução: A teoria aponta para a existência de possíveis elos entre a ideologia partidária e as políticas públicas migratórias, afirmando que, em princípio, valores associados à direita tendem a, com base no nacionalismo, restringir mais as dinâmicas de imigração do que aquelas ligadas à axiologia da esquerda, ancorada no universalismo. A ideologia partidária afeta os padrões de imigração na União Europeia? Este artigo testa a hipótese de que quanto maiores os valores na ideologia (governos de direita), menor o número de migrantes para aquele país específico. Materiais e Métodos: O desenho da pesquisa replica dados secundários do ParlGov e do Comparative Manifesto Project. Também usamos dados do Global Bilateral Migration Database e do Bilateral Migration Matrix. Além da estatística descritiva, examinamos a relação entre ideologia e fluxos migratórios. Nós estimamos dois modelos de regressão para lidar com as seguintes variáveis dependentes: migração líquida e população de refugiados por país ou território de asilo. Resultados: Usando dados do ParlGov, Manifesto e QoG, a estatística descritiva enfatizou uma cartografia muito heterogênea de características políticas, ideologia e migração nos países da União Europeia. A primeira análise de regressão usando dados agregados sugere que quanto maiores os valores de ideologia por país (orientada para a direita), menor o número de pessoas que entram naquele país. No entanto, os resultados de nossa análise estatística desagregada, particularmente o Modelo 1, não indicam nenhum efeito da ideologia de gabinete sobre a migração líquida. No que diz respeito à categoria de refugiados para imigrantes, nossos resultados sugerem que os governos nacionais orientados para a direita são menos receptivos aos refugiados. O Modelo 2 afirmou que um aumento de um ponto na ideologia está associado a uma redução média de 13% no número de refugiados que entram no país. Discussão: Nosso estudo avança o entendimento atual sobre a relação entre ideologia partidária e padrões de imigração. No entanto, os resultados da análise de regressão mostram evidências limitadas em favor da nossa hipótese de que quanto mais à direita o governo no espectro ideológico, menor o número de refugiados aceitos no país. No entanto, esta análise destina-se apenas a mostrar uma relação entre ideologia e migração. Reivindicações causais devem ser interpretadas com cautela. PALAVRAS-CHAVE: União Europeia; governo; ideologia; migração; partidos políticos.